2020
DOI: 10.1503/cmaj.191012
|View full text |Cite
|
Sign up to set email alerts
|

Oral glucocorticoids and incidence of hypertension in people with chronic inflammatory diseases: a population-based cohort study

Abstract: BACKGROUND: Only a few populationbased studies have examined the association between glucocorticoids and hypertension, with inconsistent results. We aimed to investigate the effect of oral glucocorticoids on incidence of hypertension in adults with chronic inflammatory diseases. METHODS: We analyzed electronic health records from 389 practices in England during 1998-2017 of adults diagnosed with any of 6 chronic inflammatory diseases but with no previous diagnosis of hypertension. We used glucocorticoid prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…We defined several time-variant glucocorticoid variables to quantify current and cumulative drug exposure: (1) ever use from 1 year (2 or 5 years in additional sensitivity analyses) prior to follow-up start (binary variable); (2) current daily use (i.e., whether or not the patient was prescribed glucocorticoids at a given time point [binary variable]); (3) current daily dose per 5 mg/day with 0 value when medication was not prescribed (continuous and categorical variables: non-use, 1 to 4.9 mg, 5.0 to 14.9 mg, 15.0 to 24.9 mg, �25.0 mg/day); and (4) cumulative dose since 1 year (2 or 5 years in additional sensitivity analyses) prior to follow-up start per 1,000 mg (i.e., sum of the total dose prescribed up to that point divided by 1,000; considered as continuous and categorical variables: non-use, 1 to 959 mg, 960 to 3,054 mg, 3,055 to 7,299 mg, and �7,300 mg; as defined previously [19][20][21][22]).…”
Section: Oral Glucocorticoid Exposurementioning
confidence: 99%
“…We defined several time-variant glucocorticoid variables to quantify current and cumulative drug exposure: (1) ever use from 1 year (2 or 5 years in additional sensitivity analyses) prior to follow-up start (binary variable); (2) current daily use (i.e., whether or not the patient was prescribed glucocorticoids at a given time point [binary variable]); (3) current daily dose per 5 mg/day with 0 value when medication was not prescribed (continuous and categorical variables: non-use, 1 to 4.9 mg, 5.0 to 14.9 mg, 15.0 to 24.9 mg, �25.0 mg/day); and (4) cumulative dose since 1 year (2 or 5 years in additional sensitivity analyses) prior to follow-up start per 1,000 mg (i.e., sum of the total dose prescribed up to that point divided by 1,000; considered as continuous and categorical variables: non-use, 1 to 959 mg, 960 to 3,054 mg, 3,055 to 7,299 mg, and �7,300 mg; as defined previously [19][20][21][22]).…”
Section: Oral Glucocorticoid Exposurementioning
confidence: 99%
“…regional musculoskeletal complaints) not necessarily relating to activity of the index disease [ 34 , 35 ]. This likely perpetuates corticosteroid prescribing despite guidelines and trial-based evidence of associated diabetes, hypertension and cardiovascular disease risk in RA patients [ 9 , 10 , 12 ]. It may also mask symptoms of poor RA disease control.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for the higher observed prevalence of comorbidities in UC patients are beyond the scope of this study but may be associated with corticosteroids’ side effects. For example, a study of six inflammatory diseases (including 25,162 patients with inflammatory bowel disease) found that cumulative dose of oral glucocorticoids was associated with increased incidence of hypertension [ 29 ]; another study of patients with rheumatoid arthritis found that daily dose of ≥ 7.5 mg of glucocorticoids was associated with a hazard ratio of 2.33 (95% CI 1.68–3.22) for incident diabetes compared with patients not prescribed oral glucocorticoids [ 30 ]. Osteoporosis is also an important consideration for patients with increased dose and duration of corticosteroids exposure [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%